The Influence of Vested Interests on Healthcare Legislation in the USA, 2009–2010. Issue 2 (2nd April 2016) - Spithoven, Antoon
Abstract: Collective lobbying organizations and some big companies acted as cautious partners in the design of the Affordable Care Act of the Obama Administration. In addition to being consulted by government executives, these entities intensively lobbied legislators. The qualitative and statistical analysis I conduct here shows a positive impact of healthcare lobbying. Collective lobbying organizations have a significant impact on lawmaking and complementary lobbying enhances their impact. However, not all (disjointed) lobbying is successful. Perspective-based distortion might explain why organizations lobby on issues against all odds of ever being effective.